The principle of reliance as a criterion for delimiting the criminal responsibility of physicians - Contreras Chaimovich, Lautaro Camilo (Acta Bioethica, 2019)
In the present article, the author analyzes the pre-requisites and boundaries of the principle of reliance as a criterion for determining the due care that can be demanded from physicians. For that purpose, a distinction is made between horizontal and vertical division of labour. Regarding horizontal division, the relevance of a clear delimitation of scopes of responsibility for the principle of reliance to apply is highlighted. Regarding vertical division, an explanation about delegation of medical activities to nurses and paramedic auxiliaries (contemplated in indent 2 of article 113 of the Sanitary Code) is offered, as well as one about the duties of selection, instruction and supervision that must be fulfilled for the physicians to be allowed to trust in the correct execution of the delegated tasks.